Становление научно-технического центра твердых сплавов концерна «Алкон» НАН Украины - Бондаренко, В.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The development process of the ALCON Hard Alloy Science and Technology Center of NAS of Ukraine is described. It was shown that during 1952 – 2007 years from the very small productive area a well equipped and with highly skilled personnel the science and technology center was grown. It solves complicated scientific problems and productive tasks in the range of the powders producing to bulky hard metal products (the diameter and the lenth is up to 500 mm) with the potential productive possibility up to 80 tons of hard alloys a year.